Methods of Teaching Early Literacy - Gurjar, Nandita; Meacham, Sohyun; Beecher, Constance (Open textbook library., 2023)
This textbook covers theories, teaching strategies, and instructional materials pertinent to teaching reading and writing in grades PK-3, with an emphasis on integrating reading, writing, speaking, and listening, as well as integration across content areas while addressing diversity and inclusion.